2011
DOI: 10.3174/ajnr.a2855
|View full text |Cite
|
Sign up to set email alerts
|

A Distinct MR Imaging Phenotype in Amyotrophic Lateral Sclerosis: Correlation between T1 Magnetization Transfer Contrast Hyperintensity along the Corticospinal Tract and Diffusion Tensor Imaging Analysis

Abstract: BACKGROUND AND PURPOSE:In the search for a diagnostic marker in ALS, we focused our attention on the hyperintense signal intensity in T1 MTC MR images along the CST, detected in some patients and not found in other patients with ALS and in control subjects. The aim of this study was to investigate the relationship between the hyperintense signal intensity in T1 MTC images and white matter damage. To this purpose, we studied potential heterogeneities in DTI values within our patients by using TBSS without a pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 52 publications
5
20
0
Order By: Relevance
“…See Figure 1 for FA, RD, and AD results. These results are in line with previous findings in the literature (26)(27)(28).…”
Section: Tbss Dti: Decreased Fa and Increased Ad And Rd In Als Patientssupporting
confidence: 83%
“…See Figure 1 for FA, RD, and AD results. These results are in line with previous findings in the literature (26)(27)(28).…”
Section: Tbss Dti: Decreased Fa and Increased Ad And Rd In Als Patientssupporting
confidence: 83%
“…The posterior limb of the internal capsule is the place where the most pronounced decrease in FA and increase in MD have been demonstrated 15,38 . Decreased FA in patients with ALS has been found to correlate with disease severity 11,42,43 , rate of disease progression 44 , and clinical 38,45 and electrophysiological 46 measures of UMN involvement. The analysis of FA and MD support the view that ALS is a multisystem degenerative disease in which abnormalities of extra-motor areas play an important role in its pathophysiology, given that it has been possible to demonstrate that the abnormalities are not restricted to the motor tract (Fig 3) but also extend to extra-motor regions, including the corpus callosum, frontal and parietal WM, insula, and hippocampal formation 14,38 .…”
Section: Non-conventional Mrimentioning
confidence: 99%
“…Previous reports have supported that MRI should be included in the workup of any patient with weakness and pyramidal signs [9][10][11] . Furthermore, some authors have suggested new MR techniques for the list of potential ALS biomarkers 4,[12][13][14] .…”
mentioning
confidence: 99%
“…Most DTI studies of ALS have been cross-sectional studies at a single time-point, which have focused on abnormalities in the white matter (WM) of the motor system (Carrara, Carapelli et al 2012, Kwan, Meoded et al 2013, Müller, Turner et al 2016 (Sood, Gupta et al 2010) and NAA/creatine , along CST.…”
Section: Serial Mri Studiesmentioning
confidence: 99%
“…MD is used clinically to identify damage in white matter that appears normal on structural imaging (Werring, Clark et al 1999, Bammer, Augustin et al 2000. Most DTI studies of ALS have been cross-sectional studies at a single time-point and have focused on abnormalities in the white matter (WM) of the motor system (Carrara, Carapelli et al 2012, Kwan, Meoded et al 2013, Müller, Turner et al 2016. However, some studies have reported the involvement of association tracts and subcortical structures (Pettit, Bastin et al 2012).…”
Section: Introductionmentioning
confidence: 99%